2015
DOI: 10.1039/c5ay01007a
|View full text |Cite
|
Sign up to set email alerts
|

A highly selective “turn-on” fluorescent chemosensor based on 8-aminoquinoline for detection of Zn2+

Abstract: A new "turn-on" fluorescent probe based on 8-aminoquinoline for Zn 2+ was designed, synthesized and characterized. The sensor showed excellent selectivity and sensitivity with a fluorescence enhancement to Zn 2+ over other cations in CH3OH-H2O solution. Detection limit of Zn 2+ by HAQT reached 2.56×10 -7 M. The binding ratio of HAQT-Zn 2+ complex was determined to be 1:1 according to the Job plot. The mechanism of HAQT for the recognition of Zn 2+ has been investigated by FT-IR, 1 H NMR and MS analyses. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…In determining the binding studies between receptor 8-amidoquinoline compounds, all the papers reviewed were reported on characterization spectroscopy, fluorescence titration, and UV-Vis titration [42,112,118]. They seek binding mode via job plot method and binding constant (K d ) or association constant (K a ).…”
Section: Binding Studies Of 8-amidoquinoline Probes Via Solution Studiesmentioning
confidence: 99%
“…In determining the binding studies between receptor 8-amidoquinoline compounds, all the papers reviewed were reported on characterization spectroscopy, fluorescence titration, and UV-Vis titration [42,112,118]. They seek binding mode via job plot method and binding constant (K d ) or association constant (K a ).…”
Section: Binding Studies Of 8-amidoquinoline Probes Via Solution Studiesmentioning
confidence: 99%
“…Excellent sensitivity and selectivity with 'turn-on' fluorescent probe 46 ( Figure 44) has been detected for Zn 2 + ions. [74] The absorption spectrum of probe 46 displayed an absorption maximum at 239 nm with two broad absorption peaks at (Figure 45) which exhibited a weak fluorescence peak at the wavelength of 386 nm when excited at λ ex = 296 nm owing to PET effect. [75] Upon the introduction of Zn 2 + ions, the fluorescence intensity of 47 has been increased by 3.5-fold, with the emission peak shifted from the region of 386 to 422 nm.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…In determining the binding studies between receptor 8-amidoquinoline compounds, all the papers reviewed were reported on characterization spectroscopy, fluorescence titration, and UV-Vis titration [20,43,73]. They seek for binding mode via job plot method and binding constant (Kd) or association constant (Ka).…”
Section: Binding Studies Of 8-amidoquinoline Probes Via Solution Workmentioning
confidence: 99%
“…The only difference in those studies is the interference metals, and the metal ratio to zinc used. Nevertheless, certain studies [20,47,50,58,60,64,65,67] demonstrated that the sensing probe could be used in a real sample due to the metals involved not present or least in biological applications. These exhibited 8-amidoquinoline derivatives are selective to zinc detection due to minor interferences issues.…”
Section: Interferences Of Other Competitive Metal Cationsmentioning
confidence: 99%
See 1 more Smart Citation